CEO Compensation and Board Structure Revisited - GUTHRIE, KATHERINE; SOKOLOWSKY, JAN; WAN, KAM‐MING (Journal of Finance, 2012)
ABSTRACT Chhaochharia and Grinstein estimate that CEO pay decreases 17% more in firms that were not compliant with the recent NYSE/Nasdaq board independence requirement than in firms that were compliant. We document that 74% of this magnitude is attributable to two outliers of 865 sample firms. In addition, we find that the compensation committee independence requirement increases CEO total pay, particularly in the presence of effective shareholder monitoring. Our evidence casts doubt on the effectiveness of independent directors in constraining CEO pay as suggested by the managerial power hypothesis.